PENDETEKSIAN KETINGGIAN PERMUKAAN ZAT CAIR AIR MENGGUNAKAN MICROCONTROLER AT89C51 - Priyono Yulianto (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2008)
AbstractSince the traditional water level controller has the above-mentioned problems, many people have tried to detect and control the water level in a digital manner. The usually way is to install a sensor to detect the water level of the basement tank. When the water level is less than a prescribed value, the power of the alarm or led indicator will be running and shut down to prevent burning the motor. To deal with the above disadvantages, the 89C51Atmel Microcontroller type Â will be used to design a circuit for water level detection and control. Recently, the electronic field develop rapidly especially in creating water level controller. Many competitions have conducted to compare technology, from traditional water level controller until industries are never bored to talk. Industrially, automotic water level controller needed in order to make the work more efficient, then it save cost of a production. This water level controller designed by Microcontroller AT89C51, variable resistor and float ball sensor as water level detector and it also have Analog to Digital Converter (ADC) circuit as signal analog to digital. Keywords: Microcontroller AT89C51, variable resistor sensor, Analog to Digital Converter